A surface molecularly imprinted polymer as chiral stationary phase for chiral separation of 1, 1′‐binaphthalene‐2‐naphthol racemates. Issue 7 (25th May 2017) - Dong, Hongxing; Zhang, Danxia; Lin, Hailong; Wang, Yudan; Liu, Lijia; Zheng, Meixia; Li, Xiaobo; Zhang, Chunhong; Li, Junqing; Zhang, Peng; So, Juhyok
Abstract: Acrylamide (AM) was copolymerized with ethylene glycol dimethacrylate (EGDMA) in the presence of ( R )‐1, 1′‐binaphthalene‐2‐naphthol (BINOL) as the template molecules on the surface of silica gel by a free radical polymerization to produce a chiral stationary phase based on the surface molecularly imprinted polymer (SMIP‐CSP). The SMIP‐CSP showed a much better separation factor ( α = 4.28) than the CSP based on the molecularly imprinted polymer (MIP‐CSP) without coating on the silica gel ( α = 1.96) during the chiral separation of BINOL enantiomers by high‐performance liquid chromatography. The influence of the pretreatment temperature and the content of the template molecule (( R )‐BINOL) of the SMIP‐CSP, and the mobile phase composition on the separation of the racemic BINOL were systematically investigated. Abstract :